Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - FENNEMA-NOTESTINE, Christine (2013)
MRI alterations in the cerebral white (WM) and gray matter (GM) are common in HIV infection, even during successful combination antiretroviral therapy (CART), and their pathophysiology and clinical significance are unclear. We evaluated the association of these alterations with recovery of CD4+ T-cells. Seventy-five HIV-infected (HIV+) volunteers in the CNS HIV Anti-Retroviral Therapy Effects Research (CHARTER) study underwent brain MRI at two visits. Multi-channel morphometry yielded volumes of total cerebral WM, abnormal WM, cortical and subcortical GM, and ventricular and sulcal CSF. Multivariable linear regressions were used to predict volumetric changes with change in current CD4 and detectable HIV RNA. On average, the cohort (79% initially on CART) demonstrated loss of total cerebral WM alongside increases in abnormal WM and ventricular volumes. A greater extent of CD4 recovery was associated with increases in abnormal WM and subcortical GM volumes. Virologic suppression was associated with increased subcortical GM volume, independent of CD4 recovery. These findings suggest a possible link between brain alterations and immune recovery, distinct from the influence of virologic suppression. The association of increasing abnormal WM and subcortical GM volumes with CD4+ T-cell recovery suggests that neuroinflammation may be one mechanism in CNS pathogenesis.